2023
DOI: 10.5483/bmbrep.2022-0149
|View full text |Cite
|
Sign up to set email alerts
|

Elevated expression of exogenous RAD51 enhances the CRISPR/Cas9-mediated genome editing efficiency

Abstract: Genome editing using CRISPR-associated technology is widely used to modify the genomes rapidly and efficiently on specific DNA double-strand breaks (DSBs) induced by Cas9 endonuclease. However, despite swift advance in Cas9 engineering, structural basis of Cas9-recognition and cleavage complex remains unclear. Proper assembly of this complex correlates to effective Cas9 activity, leading to high efficacy of genome editing events. Here, we develop a CRISPR/Cas9-RAD51 plasmid constitutively expressing RAD51, whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…Notably, the combined use of purified RAD51 protein (RAD51 recombinase) and CRISPR-Cas9 reagents has recently been shown to significantly increase the efficiency of homozygous KI in mouse embryos [65]. Park et al [66] reported similar observations. Notably, Ma et al [67] recently developed miCas9 by fusing a minimal motif consisting of 36 amino acids (encoded by BReast CAncer gene 1 exon 27) to Streptococcus pyogenes Cas9 (SpCas9).…”
Section: I-gonad Targeted Two-cell Embryosmentioning
confidence: 88%
“…Notably, the combined use of purified RAD51 protein (RAD51 recombinase) and CRISPR-Cas9 reagents has recently been shown to significantly increase the efficiency of homozygous KI in mouse embryos [65]. Park et al [66] reported similar observations. Notably, Ma et al [67] recently developed miCas9 by fusing a minimal motif consisting of 36 amino acids (encoded by BReast CAncer gene 1 exon 27) to Streptococcus pyogenes Cas9 (SpCas9).…”
Section: I-gonad Targeted Two-cell Embryosmentioning
confidence: 88%